Determination of crack extension resistance of concrete from boundary effect model. (1st March 2021) - Zhao, Yanhua; Liu, Yang; Xu, Bohan
Highlights: R -curve consists of a rising part and a horizontal part due to crack propagation. Proposed R -curve is independent of specimen size when 0.2 ≤  α 0  ≤ 0.9. Aggregate effect is included in the proposed R -curve in terms of dmax . Abstract: The fracture behavior of concrete can be described by an R -curve, which represents the ability of concrete to resist crack propagation. In this study, the R -curve is defined as the envelope of the energy release rates in the critical state and is constructed on the basis of the boundary effect model. Two fracture parameters are introduced for constructing the R -curve, namely, the fracture energy Gf and the equivalent crack extension cf in an infinitely large specimen, and these two vital parameters can be obtained from testing specimens of different sizes. One of the greatest features of the proposed R -curve is that the influence of concrete aggregate is explicitly manifested in the R -curve expression in terms of the maximum aggregate size. The theoretically derived ascending branch of the R -curve is fitted using a unified function for three-point bending specimens with varying values of the initial crack length relative to the specimen depth (between 0.2 and 0.9). The developed R -curve approach is applied to the tested three-point bending notched concrete beams, and the predicted load-displacement responses are found to agree with the experimental curves. It is also shown that the results are not sensitive to the choice of the discrete number β, which is included in the R -curve expression to address the linkage between the fictitious crack growth and coarse aggregate structures of concrete.